A model for periodic blazars - Sobacchi, Emanuele; Sormani, Mattia C.; Stamerra, Antonio (Monthly notices of the Royal Astronomical Society, 2016)
We describe a scenario to explain blazar periodicities with time-scales of ∼ few years. The scenario is based on a binary supermassive black hole (SMBH) system in which one of the two SMBHs carries a jet. We discuss the various mechanisms that can cause the jet to precess and produce corkscrew patterns through space with a scale of ∼ few pc. It turns out that the dominant mechanism responsible for the precession is simply the imprint of the jet-carrying SMBH orbital speed on the jet. Gravitational deflection and Lense-Thirring precession (due to the gravitational field of the other SMBH) are second-order effects. We complement the scenario with a kinematical jet model which is inspired to the spine-sheath structure observed in M87. One of the main advantages of such a structure is that it allows the peak of the synchrotron emission to scale with frequency according to νF ∝ νξ as the viewing angle is changed, where ξ is not necessarily 3 or 4 as in the case of jets with uniform velocity, but can be ξ ∼ 1. Finally, we apply the model to the source PG1553+113, which has been recently claimed to show a Tobs = (2.18 ± 0.08) yr periodicity. We are able to reproduce the optical and gamma-ray light curves and multiple synchrotron spectra simultaneously. We also give estimates of the source mass and size.